Habitat use and migratory behaviour of pikeperch Sander lucioperca in Lithuanian and Latvian waters as inferred from otolith Sr:Ca ratios. (5th November 2017) - Ložys, Linas; Shiao, Jen-Chieh; Iizuka, Yoshiyuki; Minde, Atis; Pūtys, Žilvinas; Jakubavičiūtė, Eglė; Dainys, Justas; Gorfine, Harry; Tzeng, Wann-Nian
Abstract: Determination of the geographic boundaries that define a stock is a key challenge in fisheries management. Acquiring an understanding of spatial distribution and migration patterns of pikeperch Sander lucioperca populations in the south-eastern Baltic Sea region would help to delineate the stocks and contribute towards sustainable exploitation of the population. In this study, habitat use and migratory behaviour of S. lucioperca were inferred from otolith Sr:Ca ratios obtained via an Electron Probe Micro-Analyzer. S. lucioperca collected from the inland Kaunas City water reservoir, where downstream migration is precluded by a hydro-power plant, consistently showed a freshwater signature in their otoliths throughout their life history. In contrast, those collected from the Baltic Sea and Curonian Lagoon in Lithuania, and the lower reaches of the Daugava River in Latvia had ratios indicative of movement between fresh and brackish water habitats. Although S. lucioperca can inhabit brackish water bodies, they predominantly reside and reproduce in freshwater systems. It is thought that periodic post-spawning migration to the sea during spring is related to better foraging conditions and perhaps as a strategy for shedding ectoparasites. Currently, catch quotas apply only to those S. lucioperca taken from the Curonian Lagoon and not the Baltic Sea. Frequent migration between freshwater habitats and the Baltic Sea suggest that S. lucioperca stocks from a given river/estuary system should be considered as a single management unit despite individual differences in migratory behaviour. The extent to which migration into the Baltic Sea could potentially compromise the effectiveness of catch quotas was the main issue which initiated this study.